Physical, textural and crystallization characteristics of different chain length diacylglycerol-based solid fats - Zhou, Jun; Mao, Yilin; Lee, Yee‐Ying; Lai, Oi‐Ming; Tan, Chin‐Ping; Cheng, Jianqiang; Wang, Yong; Zhang, Zhen (Wiley, 2023)
Compared with conventional plant oils, diacylglycerol (DAG)-based fats exhibit a higher melting point and could serve as a solid base oil for preparing specialty fats. In this study, different chain length DAG-based solid fats were prepared, and the influences of acyl groups on the physical property, crystal microstructure, and crystallization kinetics of the binary solid fat phase were explored. The slipping melting point (SMP) of obtained medium chain-DAG (MCD-fats), medium-long chain-DAG (MLCD-fats), and long chain-DAG (LCD-fats) fats were 35.67, 40.70, and 52.30°C, and their original β′ crystal content were 46.3, 56.1, and 66.9, respectively. The solid fat content (SFC) profiles and crystallization properties were significantly affected as the fatty acid chain length and acylglycerols compositions changes. The microstructure of crystal in DAG-fats got denser slowly during storage. DAG can delay the translation of crystal form and stabilize β′ crystal form, which is related to their three-dimensional crystalline network changes. The hardness of MCD-fats and LCD-fats were higher than that of MLCD-fats because of the acylglycerol compositions as well as fat crystals in DAG-fats. Applying high melting point DAG as a novel base stock has an immense potential value in the production of specialty fats with low saturated fat, high stability, and decent operability.